2010
DOI: 10.1016/j.ajhg.2010.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Population Analysis of the 4q and 10q Subtelomeres Identifies Only Four Discrete Interchromosomal Sequence Transfers in Human Evolution

Abstract: Subtelomeres are dynamic structures composed of blocks of homologous DNA sequences. These so-called duplicons are dispersed over many chromosome ends. We studied the human 4q and 10q subtelomeres, which contain the polymorphic macrosatellite repeat D4Z4 and which share high sequence similarity over a region of, on average, >200 kb. Sequence analysis of four polymorphic markers in the African, European, and Asian HAPMAP panels revealed 17 subtelomeric 4q and eight subtelomeric 10qter haplotypes. Haplotypes that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
140
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(163 citation statements)
references
References 34 publications
9
140
3
Order By: Relevance
“…As reported, all 4q subtelomeres originate from only four discrete interchromosomal sequence transfers during human evolu- tion, and haplotypes with mixtures of 4q-and 10q-specific sequences represent intermediate structures in the transition from 4q to 10q subtelomeres. 10 We also found that in this family, a 4qB variant resided on chromosome 10, confirming the same detection in other populations, 10 and further suggesting that the breakpoint of the D4Z4 repeat was distal to the 4qA and 4qB variants. The pathophysiological pathway from 4q35 deletion together with the 4qA variant to the clinical picture of FSHD is unclear.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…As reported, all 4q subtelomeres originate from only four discrete interchromosomal sequence transfers during human evolu- tion, and haplotypes with mixtures of 4q-and 10q-specific sequences represent intermediate structures in the transition from 4q to 10q subtelomeres. 10 We also found that in this family, a 4qB variant resided on chromosome 10, confirming the same detection in other populations, 10 and further suggesting that the breakpoint of the D4Z4 repeat was distal to the 4qA and 4qB variants. The pathophysiological pathway from 4q35 deletion together with the 4qA variant to the clinical picture of FSHD is unclear.…”
Section: Discussionsupporting
confidence: 71%
“…[3][4][5] Furthermore, several reports have confirmed that there are 4qA and 4qB variants of the 4q subtelomere, and FSHD is uniquely associated with the 4qA variant. [6][7][8][9][10] These findings add to the diagnostic challenge and pathogenetic complexity. 11 Therefore, the correct diagnosis of FSHD depends on the ability to distinguish the 4qA and 4qB variants.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the same haplotypes are also found in the duplicated FR-MAR present within the q26 region of human chromosome 10. [22][23][24] Consequently, any cell contains four copies and up to four haplotypes of the FR-MAR. All four copies of FR-MAR are attached to the NM in normal primary human myoblasts, as was previously demonstrated by in situ fluorescent hybridization on nuclear halos.…”
Section: Resultsmentioning
confidence: 99%
“…These 8nt þ haplotypes are generally not associated with the FSHD phenotype. [22][23][24] Next, we have analyzed the level of DNA methylation at four CpGs in the FR-MAR region in relation with NM attachment. One of the four CpGs, CpG 4 , was found to be 100% methylated in the NM fraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation